(untitled) (Comprehensive Journal of Science, 2026)
The late 15th century witnessed widespread religious persecution and expulsions of Jews from the Iberian Peninsula, particularly after the issuance of the Alhambra Decree in 1492. These events prompted successive waves of Jewish migration toward the Islamic Maghreb, where more tolerant Islamic regimes offered relative refuge. Jewish communities played a vital role in the economic and cultural life of North African societies. The Ottoman Empire adopted a notably positive stance toward these migrations, recognizing the value of Jewish migrants as skilled contributors in trade and industry. This abstract explores the causes and routes of migration, the responses of Maghrebi states and the Ottoman Empire, and the religious, political, and economic dimensions of this historical movement.